2022
DOI: 10.1002/qua.27008
|View full text |Cite
|
Sign up to set email alerts
|

Si6C18: A bispentalene derivative with two planar tetracoordinate carbons

Abstract: Here we show that substituting the ten protons in the dianion of a bispentalene derivative (C18H102−) by six Si2+ dications produces a minimum energy structure with two planar tetracoordinate carbons (ptC). In Si6C18, the ptCs are embedded in the terminal C5 pentagonal rings and participate in a three‐center, two‐electron (3c‐2e) Si‐ptC‐Si σ‐bond. Our exploration of the potential energy surface identifies a triphenylene derivative as the putative global minimum. Nevertheless, robustness to Born–Oppenheimer mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 73 publications
0
5
0
Order By: Relevance
“…This research delves into the intricate processes of designing and examining the PES of polycyclic systems comprising over twenty atoms featuring ptCs. To address this challenge, we employed a proven design principle [23,[29][30][31][32][33][34][35], to computationally formulate a derivative of Naphtho[1,2-b:4,3-b′:5,6-b′′:8,7-b′′′′]tetrathiophene. This design procedure initiated substituting sulfur atoms with CHunits.…”
Section: Design Of the Si8c22 Cluster Incorporating Four Ptcsmentioning
confidence: 99%
See 1 more Smart Citation
“…This research delves into the intricate processes of designing and examining the PES of polycyclic systems comprising over twenty atoms featuring ptCs. To address this challenge, we employed a proven design principle [23,[29][30][31][32][33][34][35], to computationally formulate a derivative of Naphtho[1,2-b:4,3-b′:5,6-b′′:8,7-b′′′′]tetrathiophene. This design procedure initiated substituting sulfur atoms with CHunits.…”
Section: Design Of the Si8c22 Cluster Incorporating Four Ptcsmentioning
confidence: 99%
“…This substitution was designed to preserve the π-aromatic circuits inherent in the parent aromatic hydrocarbons. This strategy was initially tested on derivatives of small aromatic hydrocarbons, each featuring one or two ptCs [23,[29][30][31][32][33][34][35]. A striking feature of these ptC systems is their global π-aromaticity and three-center, two-electron (3c-2e) E-ptC-E bonds that display localized -aromaticity.…”
Section: Introductionmentioning
confidence: 99%
“…This research delves into the intricate processes of designing and examining the PES of polycyclic systems comprising over twenty atoms featuring ptCs. To address this challenge, we employed a proven design principle [23,[29][30][31][32][33][34][35] Despite not achieving the global minimum (GM), the resultant cluster (1) was a local minimum on the PES. This allowed us to assess a simple but effective strategy to explore its PES (see below).…”
Section: Design Of the Si 8 C 22 Cluster Incorporating Four Ptcsmentioning
confidence: 99%
“…This substitution was designed to preserve the π-aromatic circuits inherent in the parent aromatic hydrocarbons. This strategy was initially tested on derivatives of small aromatic hydrocarbons, each featuring one or two ptCs [23,[29][30][31][32][33][34][35]. A striking feature of these ptC systems is their global π-aromaticity and three-center, two-electron (3c-2e) E-ptC-E σ-bonds that display a localized σ-aromaticity.…”
Section: Introductionmentioning
confidence: 99%
“…20 These compounds, in conjunction with those hypercoordinated carbon systems, have been studied extensively because of the breaking of the traditional rules that indicate that carbon should form four covalent bonds in a tetrahedral arrangement. [21][22][23][24][25][26][27][28][29] However, to the authors' knowledge, no systematic study of hypercoordinated carbon compounds containing C-Ng s-bonds has been reported to date. The only hypercoordinated compound containing a noble gas atom was reported by Olah and coworkers, who predicted the structure and dissociation in the CH 4 2+ and He components.…”
Section: Introductionmentioning
confidence: 99%